Implication of inter-joint coordination on the limb symmetry index measured during the seated single-arm horizontal push test - Blache, Y.; Degot, M.; de Sousa, T.; Rogowski, I. (Frontiers in Sports and Active Living, 2025)
IntroductionThe seated single-arm horizontal push test (SSAHPT) could be used to assess unilateral upper-extremity power. While superior performance of the dominant side compared to the nondominant one (LSI) is often observed, causes of this bilateral imbalance remain unclear. This study aimed to assess the influence of upper-extremity dominance on both inter-joint coordination and joint contribution in SSAHPT.MethodsTwenty-five healthy male athletes were fitted with reflective markers and performed SSAHPT with the dominant and nondominant sides. Humerothoracic, elbow and wrist joint contributions to the horizontal medicine ball velocity were computed. The temporal occurrence of joint peak contribution was used to assess inter-joint coordination.ResultsThe temporal occurrence of joint peak contribution occurred in a proximo-to-distal sequence at the dominant side, while at the nondominant side, joint peak contribution first occurred at shoulder, then simultaneously at elbow and wrist. The elbow joint contributed the most to the horizontal medicine ball velocity, but its relative contribution was significantly greater for the nondominant limb than the dominant one (p < 0.05).DiscussionThese findings highlight that SSAHPT bilateral asymmetry is explained by a change in motor patterns, as inter-joint coordination and contribution, between the dominant and nondominant sides. From a practical perspective, our findings suggest that for healthy athletes, firstly the LSI observed during SSAHPT may not be used as a good indicator of bilateral imbalance in upper-extremity power, and secondly SSAHPT performance reflects primarily elbow joint velocity capacities and then shoulder ones.